Impact of the third national 'Be Clear on Cancer' Breast Cancer in Women over 70 Campaign on general practitioner attendance and referral, diagnosis rates and prevalence awareness. (5th April 2022) - Eberhardt, Judith; Bright, Chloe J.; Gildea, Carolyn; Adeghe, Osa; Mak, Vivian; Paley, Lizz; Ling, Jonathan; Elliss‐Brookes, Lucy
Abstract: Objective: More than a third of women diagnosed with breast cancer in England, and over half of those who die from it, are over 70. The Be Clear on Cancer Breast Cancer in Women over 70 Campaign, running three times, 2014–2018, aimed to promote early diagnosis of breast cancer in England by raising symptom awareness and encouraging women to see their general practitioner (GP) without delay. We sought to establish whether the third campaign had successfully met its aims. Methods: Metrics covering the patient pathway, including symptom awareness, attending a GP practice with symptoms, urgent GP referral, diagnosis and stage of cancer, were assessed using national cancer databases and two household surveys. Results: The third campaign was associated with an increase in urgent cancer referrals, and therefore mammograms and ultrasounds performed. This was associated with an increase in breast cancers diagnosed. There was a delayed effect on GP attendances. Awareness of breast cancer prevalence for the 70‐and‐over age group improved. Impact on these metrics diminished across successive campaigns. Conclusions: Future campaigns should focus on harder‐to‐reach women and include GPs as targets as this campaign showed a potential to affect referral behaviour.